Effect of Green Phoskko and Em4 Activators on Compost Making from a Mixture of Goat Manure and Tapioca Industrial Solid Waste Using the Windrow Method - Shela Septiyani; Natalina (Takaza Innovatix Labs Ltd., 2026)
Organic waste from industrial cassava peels and goat manure in Lampung, a cassava production center (39.74 million tons in 2022), often pollutes the environment through open dumping due to slow natural composting from a high C/N ratio (>33). This quantitative true experimental study aims to analyze the effect of Green Phoskko and EM4 activators on windrow composting of goat manure-cassava peel mixture (1:1 ratio). The population of all potential mixtures in Lampung; purposive total sampling yielded 9 units (3 treatments × 3 replications, 6 kg/unit). Instruments used were thermometer, pH meter, spectrophotometer for N and C-organic, descriptive analysis and ANOVA/t-test via Excel/SPSS. The results showed Green Phoskko was superior: N increased by 2.80%, C-organic decreased by 15.55%, C/N ratio 10.50, pH 6.5-7, mesophilic temperature 28-32°C on day 28, meeting SNI 7763:2018. In conclusion, Green Phoskko is more effective in accelerating the composting of lignocellulosic waste than EM4.